Factors associated with frailty among postmenopausal Chinese women from selected senior citizen associations in Kuala Lumpur and Selangor, Malaysia - Chan, Kai Sze (2019)
Frailty is defined as a decline in physiological condition and immunity against stressors events, which is common among the elderly population. Mounting evidence shows frailty among older person is highly associated with higher risk of cardiovascular and cardiovascular-related diseases, fall, physical disability, poor quality of life, increased mortality and morbidity. With the increase of proportion of older person in Malaysia attributed to longevity, it is expecting that frailty will continue to rise. Chinese female, with the longest life expectancy among different ethnicities in Malaysia, is expected to have a higher prevalence of frailty. Recognizing the importance of identifying factors associated frailty in promoting healthy ageing, the present study was undertaken to determine the prevalence of frailty and factors contributing to the risk of frailty among free-living postmenopausal Chinese women in Kuala Lumpur and Selangor. A total of 220 postmenopausal Chinese women were recruited from seven affiliates under Kuala Lumpur and Selangor branch of National Council of Senior Citizen Organisation (NACSCOM). Frailty status was ascertained based on five assessments, namely unintentional weight loss, self-reported exhaustion, slow gait speed, weak handgrip strength and low physical activity level. Respondents with one to two components was classified as pre-frailty, while those with at least three components were classified as frailty. Several anthropometry assessments (weight, height, waist circumference (WC), percentage of body fat (PBF)) and blood pressure (BP) were performed according to standard protocols while skeletal muscle mass was computed accordingly. Sociodemographic background (age, duration of menopause, duration of education and education level, marital status, occupation and monthly household income) of respondents were obtained through self-administered questionnaire, while sleeping quality, smoking behaviour, sedentary time were determined using Pittsburgh Sleeping Quality Index (PSQI) Questionnaire, Global Adults Tobacco Survey (GATS), and Global Physical Activity Questionnaire (GPAQ), respectively. Nutrients intake of respondents were quantified using a validated food frequency questionnaire while diet quality was ascertained according to compliance of intakes with Malaysian Dietary Guidelines. A total of 5 ml fasting blood samples was drawn for analysis of fasting blood glucose (FBG) and lipid profile to ascertain the presence of metabolic syndrome (MS) among the respondents. Data obtained was analyzed using IBM SPSS Statistic 22.0. Independent-sample t-test was used to determine the mean differences between respondents with and without the risk of frailty, while Pearson Chi-Square (χ2) was used to determine the association between two categorical variables. Binary logistic regression was used to determine the factors that contribute to the risk of frailty.